A Prototype TOF PET Detector Module Using a Micro-Channel Plate Photomultiplier Tube with Waveform Sampling - Kim, H. (2012)
We are exploring a large area flat panel micro-channel plate photomultiplier tube (MCP PMT) under development for an application to time-of-flight positron emission tomography (TOF PET). High speed waveform sampling with transmission-lines is adopted for reading out the signal with precise time and space information with a small number of low-power channels. As a demonstration of the concept, detector modules have been built using 2″×2″ Photonis Planacon MCP PMTs (XP85022) and prototype transmission-line (TL) boards. The signals from the MCP PMT through the transmission-lines are sampled by DRS4 evaluation boards running at 5 giga-samples per second (GS/s). The event information is extracted by processing the digitized waveforms. For experimental tests, a single 3×3×10 mm(3) LYSO crystal is optically coupled to each MCP PMT; the detector responses to 511 keV annihilation photon from a (22)Na source are measured using the data taken in coincidence mode. As a preliminary result, we obtain a position resolution of ∼2.8 mm (0.3 mm) (FWHM) along (perpendicular to) the transmission-line, ∼309 ps (FWHM) for coincidence time resolution, and ∼14% (FWHM) of energy resolution at 511 keV. This initial result gives a promise that the large area MCP PMT is applicable to TOF PET.